Review of techniques useful for the assessment of sensory small fiber neuropathies: Report from an IFCN expert group. (April 2022) - Verdugo, Renato J.; Matamala, José M.; Inui, Koji; Kakigi, Ryusuke; Valls-Solé, Josep; Hansson, Per; Nilsen, Kristian Bernhard; Lombardi, Raffaella; Lauria, Giuseppe; Petropoulos, Ioannis N.; Malik, Rayaz A.; Treede, Rolf-Detlef; et al.
Highlights: Nerve conduction studies do not evaluate function of small afferent fibers. Different techniques have been developed for evaluation of these fibers, but none of them alone is sufficient for a complete evaluation. Each clinical laboratory should develop its own set of tests for evaluation of small afferent fibers. Abstract: Nerve conduction studies (NCS) are an essential aspect of the assessment of patients with peripheral neuropathies. However, conventional NCS do not reflect activation of small afferent fibers, including Aδ and C fibers. A definitive gold standard for laboratory evaluation of these fibers is still needed and therefore, clinical evaluation remains fundamental in patients with small fiber neuropathies (SFN). Several clinical and research techniques have been developed for the assessment of small fiber function, such as (i) microneurography, (ii) laser evoked potentials, (iii) contact heat evoked potentials, (iv) pain-related electrically evoked potentials, (v) quantitative thermal sensory testing, (vi) skin biopsy-intraepidermal nerve fiber density and (vii) corneal confocal microscopy. The first five are physiological techniques, while the last two are morphological. They all have advantages and limitations, but the combined use of an appropriate selection of each of them would lead to gathering invaluable information for the diagnosis of SFN. In this review, we present an update on techniques available for the study of small afferent fibers and their clinical applicability. A summary of the anatomy and important physiological aspects of these pathways, and the clinical manifestations of their dysfunction is also included, in order to have a minimal common background.